A Critical Role of TRPM7 As an Ion Channel Protein in Mediating the Mineralization of the Craniofacial Hard Tissues - Nakano, Yukiko; Le, Michael H.; Abduweli, Dawud; Ho, Sunita P.; Ryazanova, Lillia V.; Hu, Zhixian; Ryazanov, Alexey G.; Den Besten, Pamela K.; Zhang, Yan (Frontiers in Physiology, 2016)
Magnesium ion (Mg2+) is the fourth most common cation in the human body, and has a crucial role in many physiological functions. Mg2+ homeostasis is an important contributor to bone development, however, its roles in the development of dental mineralized tissues have not yet been well known. We identified that transient receptor potential cation channel, subfamily M, member 7 (TRPM7), was significantly upregulated in the mature ameloblasts as compared to other ameloblasts through our whole transcript microarray analyses of the ameloblasts. TRPM7, an ion channel for divalent metal cations with an intrinsic serine/threonine protein kinase activity, has been characterized as a key regulator of whole body Mg2+ homeostasis. Semi-quantitative PCR and immunostaining for TRMP7 confirmed its upregulation during the maturation stage of enamel formation, at which ameloblasts direct rapid mineralization of the enamel matrix. The significantly hypomineralized craniofacial structures, including incisors, molars, and cranial bones were demonstrated by microCT analysis, von Kossa and trichrome staining in Trpm7Δkinase/+ mice. A previously generated heterozygous mouse model with the deletion of the TRPM7 kinase domain. Interestingly, the skeletal phenotype of Trpm7Δkinase/+ mice resembled those found in the tissue-nonspecific alkaline phosphatase (Alpl) KO mice, thus we further examined whether ALPL protein content and alkaline phosphatase (ALPase) activity in ameloblasts, odontoblasts and osteoblasts were affected in those mice. While ALPL protein in Trpm7Δkinase/+ mice remained at the similar level as that in wt mice, ALPase activities in the Trpm7Δkinase/+ mice were almost nonexistent. Supplemented magnesium successfully rescued the activities of ALPase in ameloblasts, odontoblasts and osteoblasts of Trpm7Δkinase/+ mice. These results suggested that TRPM7 is essential for mineralization of enamel as well as dentin and bone by providing sufficient Mg2+ for the ALPL activity, underlining the key importance of ALPL for biomineralization.